2017
DOI: 10.1038/s41598-017-02470-0
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the complexation of N-Allyl-4-(4-(N-phenylureido)benzylamino)-1,8-naphthalimide with various anions

Abstract: A new urea functionalised 4-amino-1,8-naphthalimide based fluorescent anion sensor was synthesised in 64% yield over three steps. Fluorescence and 1H NMR titrations showed that the sensor complexes strongly with acetate and dihydrogen phosphate and to a lesser extent bromide. The corresponding binding stoichiometries were examined using 1H NMR titrations. Results show that the sensor molecule initially forms 1:1 complexes through hydrogen bonding to the urea moiety, followed by secondary complexation to form h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Ureas, thioureas, amides and sulfonamides are still the most commonly used binding motifs based on hydrogen bonds. For example, a urea functionalised 4-amino-1,8-naphthalimide based fluorescent anion sensor 1 has been reported by Lenehan and co-workers [20]. The properties of ureas and thioureas appended with this fluorophore have been extensively investigated in the past by Gunnlaugsson's group [21][22][23][24][25][26][27], however the Lenehan and co-workers showed that sensor 1 is able to interact with acetate, dihydrogen phosphate and bromide in hydrated DMSO with an on-off fluorescence response (Fig.…”
Section: Hydrogen Bond-based Chemosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ureas, thioureas, amides and sulfonamides are still the most commonly used binding motifs based on hydrogen bonds. For example, a urea functionalised 4-amino-1,8-naphthalimide based fluorescent anion sensor 1 has been reported by Lenehan and co-workers [20]. The properties of ureas and thioureas appended with this fluorophore have been extensively investigated in the past by Gunnlaugsson's group [21][22][23][24][25][26][27], however the Lenehan and co-workers showed that sensor 1 is able to interact with acetate, dihydrogen phosphate and bromide in hydrated DMSO with an on-off fluorescence response (Fig.…”
Section: Hydrogen Bond-based Chemosensorsmentioning
confidence: 99%
“…Fig. 22. a) Schematic presentation of photoacoustic (PA) imaging by X-Y scanning; b) photoacoustic ratio (PA750/PA680) intensity toward superoxide anion and other analytes; c) the PA750/PA680 intensity of probe 29 with different concentrations of superoxide anion and d) subsequent addition of GSH; e) redox cycles of 10 μM of probe 29 by the addition of superoxide anion(20,5, and 1 μM) followed by GSH (50, 10, and 5 μM) in PBS buffer solution (pH 7.4). Adapted with permission from Ref [68]…”
mentioning
confidence: 99%
“…According to the chemical shift change of H a on the TH (Figure 2a), K a1 of the TP5⊃TH complex was calculated as 5.62 × 10 5 M −1 (according to HypNMR software). 86 Similarly, the K a,FAP⊃AN value of the monopodial model FAP⊃AN complex was calculated via the chemical shift change of H 2 on FAP (Figure S10), which was determined as 137.19 M −1 and formed a 1:1 FAP⊃AN inclusion complex. The K a1 value of the tripodal host−guest TP5⊃TH complex is higher than K a,FAP⊃AN of the monopodial model FAP-AN complex, which indicated that a strong positive cooperative effect existed in the tripodal host− guest system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because TP5 is a tripodal host, TP5 and TH could form 1:1, 1:2, and 1:3 inclusion complexes with the corresponding association constants K a1 , K a2 , and K a3 . , Nevertheless, we can investigate the cooperative effect among the assembling process of the tripodal host TP5 with the tripodal guest TH by comparing the K a1 value of the TP5 ⊃ TH complex and the K a value of FAP ⊃ AN . According to the chemical shift change of H a on the TH (Figure a), K a1 of the TP5 ⊃ TH complex was calculated as 5.62 × 10 5 M –1 (according to HypNMR software) . Similarly, the K a, FAP ⊃ AN value of the monopodial model FAP ⊃ AN complex was calculated via the chemical shift change of H 2 on FAP (Figure S10), which was determined as 137.19 M –1 and formed a 1:1 FAP ⊃ AN inclusion complex.…”
Section: Resultsmentioning
confidence: 99%